MiR‐142a‐5p promoted osteoblast differentiation via targeting nuclear factor IA. Issue 3 (23rd July 2020) - Yuan, Hairui; Li, Mengyue; Feng, Xue; Zhu, Endong; Wang, Baoli
Abstract: miR‐142a‐5p plays critical roles in multiple biological processes and diseases, such as inflammation and tumorigenesis. However, it remains to be explored if and how miR‐142a‐5p contributes to osteoblast differentiation. In this study, our results showed that miR‐142a‐5p was highly expressed in bone tissue of mice and increased during osteogenesis in preosteoblast MC3T3‐E1 cells. Supplementing miR‐142a‐5p activity using miR‐142a‐5p agomir promoted osteogenic differentiation in stromal cell line ST2 and preosteoblastic line MC3T3‐E1. Conversely, miR‐142a‐5p antagomir, an inhibitor of endogenous miR‐142a‐5p, could reduce osteoblast differentiation in ST2 and MC3T3‐E1 cells. Nuclear factor IA (NFIA), a site‐specific transcriptional factor, was demonstrated to be directly targeted by miR‐142a‐5p. Overexpression of NFIA inhibited miR‐142a‐5p‐mediated osteoblast differentiation in ST2 cells. Furthermore, mechanism explorations revealed that Wnt/β‐catenin signaling transcriptionally regulated the expression of miR‐142a‐5p during osteogenic differentiation. β‐catenin binds to the T‐cell factor/lymphoid enhancer factor binding motif within the promoter of miR‐142 and positively regulates its transcriptional activity. Our findings suggested that miR‐142a‐5p promoted osteoblast differentiation via targeting NFIA. Abstract : 1. miR‐142a‐5p regulates osteoblast differentiation. 2. Nuclear factor IA is involved in miR‐142a‐5p‐mediated osteoblast differentiation. 3. Wnt/β‐catenin signaling regulates the expression of miR‐142a‐5p during osteogenic differentiation.